CICLO DE VIDA Y DESCRIPCIÓN DE LOS ESTADOS INMADUROS DE ASTYLUS TRIFASCIATUS GUÉRIN, 1844 (COLEOPTERA: MELYRIDAE) - Estrada M., Patricia; Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
The study of the Ufe cycle of Astylus trifasciatus Guérin, 1844 was made through laboratory and field observations. Eggs are laid during spring. Nine larval instars were recognized in laboratory conditions and a larval period a little more than two years is postulated. Larvae remain quiescent in winter. Pupation occur at the end of the third summer. Adults remain in the soil in the pupal chamber during autumn and winter and come to the surface in spring. Egg, mature larvae and pupa are described.